2020
DOI: 10.21203/rs.3.rs-39670/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3D Simulation of Radiographic Projections to Test and Reduce the Effect of Pelvic Tilt on the Accuracy of Cross-table Lateral Radiography

Abstract: Abstract Background:Cross-table lateral (CL) radiography is aconvenientandfeasible method toassess cup version angle (VA) after total hip arthroplasty; however, the pelvic tilt (PT) may contribute to its measurement inaccuracy.We sought (1) to determinethe effect of the PT on cup version measurement on CL radiography and (2) to develop a method for reducing measurement errors caused by the PT.Methods: Two groups of VAswere m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…However, it was impractical to perform multiple lateral radiographs with different X-ray incidences in patients considering the radiation exposure and ethical issues. In a previous study, a THA postoperative 3D model was built, in which some parameters, including the cup version, inclination, pelvic tilt, and incidence, were independently adjusted [20]. Independent variables and confounding factors were controlled using the standard physical model.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it was impractical to perform multiple lateral radiographs with different X-ray incidences in patients considering the radiation exposure and ethical issues. In a previous study, a THA postoperative 3D model was built, in which some parameters, including the cup version, inclination, pelvic tilt, and incidence, were independently adjusted [20]. Independent variables and confounding factors were controlled using the standard physical model.…”
Section: Methodsmentioning
confidence: 99%
“…One degree of PT changed anteversion by an average of 0.8° on the coronal plane [17]. A previous study found a similar effect of PT on cup version measurement on CL radiographs [20]. Moreover, the acetabular component version may change into or out of the conventionally de ned "safe zone" from the supine to the standing position [19].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation